Periodontal prognosis factors - Botero-Z., Leticia; Vélez-L., María Eugenia; Alvear-E., Fanny Stella (Revista Facultad de Odontología Universidad de Antioquia, 2009)
The assignation of prognosis has been made for a long time in a subjective way according to the treating expert; because, even though the classic texts traditionally name the variables that influence prognosis, each lector according to his/her personal experience interprets and weights each one differently. Throughout this revision the evidence available in order to weight each variable in a more objective way is presented. Systemic factors such as poorly controlled diabetes mellitus and heavy smoking as well as local factors such as the levels of specific bacteria and other clinical parameters such as bleeding on probing, depth on probing, level of attachment, alveolar bone loss and plaque have a good level of evidence as predictors of disease progression if analyzed together in a multifactorial model. Other systemic factors, such as the immunologic genotype of Interleukin 1, the presence of osteoporosis and psychosocial factors like stress and socio economical level are lacking evidence as reliable predictors thus the design of other trials are needed.